The Narratological Style and the Reader of Evelyn Waugh’s Early Satires (ENTHYMEMA, 2017)
The article deals with the role of the implied reader in Evelyn Waugh’s novels. An attempt will be made to define who the implied reader is and what is his position and role in fictional realm. By analysing narrative strategies and techniques within a selection of Waugh’s works, I attempt to discuss the changing relationship between author/narrator and the implied reader. I try to point that within Evelyn Waugh’s writing one can observe a simultaneous evolution of the narrator voice and the role ascribed to the implied reader. What is more, I discuss the limits of interpretation. I try to present and analyse how both the author/narrator and the text can impose limitations on the implied reader allowing him to move freely, however, within a set frame. Intertextuality is one of the focal points of the article, as I try to propose that the use of specific intertextual references in several different novels enhances the reader’s understanding of  Waugh’s fictional world. An attempt is made to prove that through analysis of different levels of understanding intertextual relation the reader takes on himself a role of creator. Furthermore, I draw attention to the places of indeterminacy. In this discussion I include both structures of indeterminacy proposed by Roman Ingarden i.e. blanks and negations, as both are needed not only to establish the interaction that takes place between text and the implied reader, but also to try to regulate such relation. An attempt will be made to explain how important filling the gaps within the text is and how completing the blanks affects the reader and the process of reading as such.
Keywords: Evelyn Waugh; Wolfgang Iser; implied reader; aesthetic response; blanks